2022
DOI: 10.1093/dnares/dsac005
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome-scale genome and transcriptomic analysis of the endangered tropical treeVatica mangachapoi(Dipterocarpaceae)

Abstract: Vatica mangachapoi is a tropical tree species native to Southeast Asia. It has long been valued as a timber species because the wood resists decay, but it is now considered vulnerable to extinction due to habitat loss and overexploitation. Here, we present the first chromosome-level genome assembly of V. mangachapoi that we created by combining data from PacBio long read sequencing with Hi-C proximity ligation and Illumina short read sequencing. The assembled genome was 456.21 Mb, containing 11 chromosome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
(87 reference statements)
2
1
0
Order By: Relevance
“…KB has united a variety of interactions, such as those between genes and proteins, elements and reactions, medications and illnesses, and organisms and cells (Kanehisa et al 2019 ). Parallel studies were reported in Vatica mangachapoi (Tang et al 2022 ), Hopea hainanensis (Huang et al 2022 ), Neesia altissima (Pratiwi et al 2022 ), C. capsularis (Satya et al 2017 ), Hibiscus hamabo siebold & zuccarini (Wang et al 2021 ), Abelmoschus esculentus (Nieuwenhuis et al 2021 ), Helicoverpa armigera (de la Paz Celorio-Mancera et al 2011 ), Gasterophilus nasalis (Zhang et al 2021 ), and Operculina turpethum (Biswal et al 2021 ). Additionally, GAEV was used to annotate the KO (Iacobas et al 2019 ; Emami-Khoyi et al 2020 ; Nand et al 2020 ; Shah et al 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…KB has united a variety of interactions, such as those between genes and proteins, elements and reactions, medications and illnesses, and organisms and cells (Kanehisa et al 2019 ). Parallel studies were reported in Vatica mangachapoi (Tang et al 2022 ), Hopea hainanensis (Huang et al 2022 ), Neesia altissima (Pratiwi et al 2022 ), C. capsularis (Satya et al 2017 ), Hibiscus hamabo siebold & zuccarini (Wang et al 2021 ), Abelmoschus esculentus (Nieuwenhuis et al 2021 ), Helicoverpa armigera (de la Paz Celorio-Mancera et al 2011 ), Gasterophilus nasalis (Zhang et al 2021 ), and Operculina turpethum (Biswal et al 2021 ). Additionally, GAEV was used to annotate the KO (Iacobas et al 2019 ; Emami-Khoyi et al 2020 ; Nand et al 2020 ; Shah et al 2021 ).…”
Section: Discussionsupporting
confidence: 75%
“…Combining the syntenic relationships and K s distributions, we found that two of the six syntenic blocks were located at the lower K s peak and four were located at the higher K s peak, indicating that the recent polyploidization event was a WGD, as reported in recent studies ( Ng et al., 2021 ; Wang et al., 2022 ), whereas the other polyploidization event was a whole-genome triplication. Thus, together with the above phylogeny, these results showed that the Dipterocarpoideae species shared a whole-genome triplication (γ) event, as reported for the common ancestor of core eudicots ( Jaillon et al., 2007 ; Tang et al., 2008a ; Jiao et al., 2012 ), and a WGD event that occurred after the divergence from T. cacao but before the earliest divergence time within Dipterocarpoideae species, consistent with previous research ( Ng et al., 2021 ; Tang et al., 2022 ).
Figure 3 Whole-genome duplication and chromosome evolutionary history in Dipterocarpoideae species.
…”
Section: Resultssupporting
confidence: 91%
“…Whereas the potential of genomics for restoring ecosystems and protecting natural habitats has been recognized, the implementation of genomic approaches has been still a challenge (Breed et al, 2019; Mohr et al, 2022). Obtaining genomes of keystone species such as Vatica mangachapoi —a keystone in a dipterocarp‐dominated tropical forest—enabled quantifying local adaptations and genetic load across populations that can be applied to planned pedigree mating and to guide replanting in drought‐afflicted areas (Tang et al, 2022). In restoration programs and conservation of threatened species occurring in disjunct ranges, quantification of the genetic variation at the landscape level is crucial to prioritize conservation under scenarios of environmental change (Gougherty et al, 2021).…”
Section: Rationale Of Initiative 2—generating Reference Genomes Of Ke...mentioning
confidence: 99%